Biological synthesis of low cytotoxicity silver nanoparticles (AgNPs) by the fungus chaetomium thermophilum—sustainable nanotechnology - Alves, Mariana Fuinhas (2022)
Shannon Applied Biotechnology Centre. Department of Applied Science. Faculty of Applied Sciences and Technology. Moylish Campus. Technological University of the Shannon. Midlands Midwest, Moylish, Ireland.